QATH’I DAN ZANNI SERTA PERAN AKAL DALAM MENGINTERPRETASIKAN NAS - Rubi Awalia; Muhammad Amri; Indo Santalia (CV. Adiba Aisha Amira, 2022)
Qath'i and zhanni in Usul fiqh are used to explain the source texts of Islamic law, be it al-Qur'an and hadith in two respects, namely al-tsubut (existence) or al-wurud (the arrival of the source truth) and al-dalalah (interpretation). In the context of qath'i and zhanny al-wurud, the scholars agree that the Qur'an and the mutawatir hadith are qath'i. However, they differ in terms of qath'i and zhanny from the side of al-dalalah. Ushul fiqh scholars state that if a religious text contains only one clear meaning and cannot open up the possibility of other interpretations, and mentions certain numbers, then the text is considered a qath'i text from the side of al-dalalah. Meanwhile, contemporary scholars argue that the concept of qath'i and zhanni al- dalalah, both the Qur'an and Hadith, cannot be seen from the clarity of the meaning of the pronunciation but also the desired essence of the pronunciation. Intellect is a thinking tool contained in humans, human reason is different from other creatures because reason is only given to humans and is not given to other creatures. This difference makes humans superior and smarter in managing their lives. Therefore, humans with clear intelligence will find God as the end result of real life